CEO voices on sustainable aviation: An analysis of environmental communication in the airline industry - Teeris Thepchalerm; Soifah Pinsuwan (Green Technologies and Sustainability, 2025)
This study analyzed chief executive officer (CEO) messages from 18 sustainable airlines to identify salient themes in their environmental reports for the year. The inductive content analysis revealed six themes: sustainability commitment, environmental initiatives, partnerships, challenges, future outlook, and motivation. The CEOs highlighted their commitment to sustainability through efforts such as procuring fuel-efficient aircraft, utilizing sustainable aviation fuel (SAF), and implementing waste management strategies. They emphasized collaboration to tackle issues like limited SAF production and the need for government support. They expressed optimism about achieving their goals, motivated by ethical considerations and strategic benefits. However, their actual environmental performance does not seem to align with their statements. This discrepancy underscores the need for airlines to ensure that their actions consistently reflect their stated commitments, fostering credibility and trust through genuine alignment with environmental goals.